Factors affecting English speaking skills of Afghan EFL tertiary learners: students’ and teachers’ perceptions - Nazifullah Nijat; Ajab Khan Sultan; S.C.Sandaran (Science and Education, 2024)
Speaking is “the process of building and sharing meaning through the use of verbal and non-verbal symbols in a variety of contexts” Speaking plays an important role in daily communication and educational purposes. In language learning; the spoken language production is viewed as the most important aspect. However, for the majority of EFL or ESL learners, speaking is the most challenging skill to master, and they cannot speak English language properly. This study aims to investigate the factors that affect Afghan tertiary level EFL learners’ English speaking. Moreover, the study focuses on students’ speaking difficulties and teachers’ reactions to the student’s oral mistakes. A quantitative research design was employed in order to achieve the objectives of the study. One hundred sixty-eight EFL learners and twenty-five EFL teachers took part in the study chosen based on stratified sampling. The findings identified a number of major factors that affect Afghan EFL learners’ speaking skills. These include noisy and crowded classes, anxiety, fear of making mistakes, fear of criticism, use of traditional teaching methods, lack of vocabulary knowledge, among others. Additionally, the major speaking problems students encounter in the class include losing face, the use of native language. The findings highlight the factors that affect Afghan students’ speaking skills. It also gives valuable insights for teachers about the factors that affect students’ speaking ability. Furthermore, it can be used as a guide for teachers in the planning and preparations for teaching and learning focusing on speaking skills for Afghan EFL tertiary students.